2018
DOI: 10.3390/ijms19123733
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Colorectal Cancer: A Challenge for Personalized Medicine?

Abstract: High inter-patient variability and high spatial heterogeneity are features of colorectal cancer (CRC). This may influence the molecular characterization of tumor tissue, now mandatory for patients with metastatic CRC who are candidates for treatment with an anti-EGFR mAb, as false-negative results can occur, leading to non optimal therapy. Moreover, temporal molecular heterogeneity during treatment is known to influence the response to therapy and prognosis. We present a literature overview of advances made in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
144
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(148 citation statements)
references
References 114 publications
(160 reference statements)
2
144
0
2
Order By: Relevance
“…Study of intratumor heterogeneity (ITH) is fundamental from both a biological and clinical perspective, to understand the genomic changes driving the evolution of the malignant process up to metastasis generation. Several studies have shown that CRCs display a consistent degree of spatial intratumor heterogeneity; particularly, three types of spatial heterogeneity of CRCs have been described: (i) ITH related to the existence of genetic differences at the level of tumor cells within the primary tumor; (ii) ITH related to differences at the level of various metastatic lesions within a single patient; (iii) ITH related to the existence of genetic differences within the cells of a single metastatic lesion (intrametastatic heterogeneity) [ 46 ].…”
Section: Tumor Heterogeneity and Metastatic Evolutionmentioning
confidence: 99%
“…Study of intratumor heterogeneity (ITH) is fundamental from both a biological and clinical perspective, to understand the genomic changes driving the evolution of the malignant process up to metastasis generation. Several studies have shown that CRCs display a consistent degree of spatial intratumor heterogeneity; particularly, three types of spatial heterogeneity of CRCs have been described: (i) ITH related to the existence of genetic differences at the level of tumor cells within the primary tumor; (ii) ITH related to differences at the level of various metastatic lesions within a single patient; (iii) ITH related to the existence of genetic differences within the cells of a single metastatic lesion (intrametastatic heterogeneity) [ 46 ].…”
Section: Tumor Heterogeneity and Metastatic Evolutionmentioning
confidence: 99%
“…At the time of diagnosis, malignant tumors contain multiple cell populations with diverse biological heterogeneity that is not restricted to primary lesions [ 32 , 33 ]. The clonal origin and genetic heterogeneity of CRCs and heterogeneity between primary tumors and liver metastases have been recently addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is a heterogeneous disease [ 1 ], molecularly and anatomically [ 2 ], that develops in a multi-step process [ 3 ] requiring the accumulation of several genetic or epigenetic mutations that lead to the gradual transformation of normal mucosa into cancer.…”
Section: Introductionmentioning
confidence: 99%